KARAKTERISTIK PEMBENTUK MOTIVASI KERJA DAN HUBUNGANNYA DENGAN KEPUASAN KERJA PEGAWAI PADA PEMERINTAH KABUPATEN BADUNG-BALI - Ni Putu Nursiani; Armanu - Thoyib; Achmad - Sudiro (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT   Basically, the company not only requires capable, competent and skillful employees but the most important thing is that they are willing to work hard and to achieve optimal performance. Employees’ capability, competence and skills would not make any improvement for the company if they are not willing to work hard to apply their capability, competence and skills and if the company gives the opportunity and appreciation for their capability, competence and skills, it would give them satisfaction and the workers will be motivated to work if they receive higher satisfaction from their job. Job satisfaction is very important since most problems occurring in organization, such as strike, demonstration, high level of absenteeism, are generally caused by job dissatisfaction. Therefore the job satisfaction of the employees in the organization should receive attention so as to preserve the healthy working condition and improve job motivation and productivity. This research was aimed at finding the characteristics that build job motivation and its relationship with the govermental employees’ job satisfaction at the Badung Regency. The population in this research is the official from the second, third and fourth echelons in the government office of the Badung Regency, by taking a sample of 100 respondents. Data were collected by distributing questionnaire. The analytic tool used in this research is Structural Equation Modeling (SEM), using the confirmatory technique, which aims at proving the theories in a model. The result of this research shows that individual and organizational characteristics have a positive impact both on the job motivation and job satisfaction while job characteristics have a negative impact on the job motivation and job satisfaction. The results also show that there is no relationship between job motivation and job satisfaction.   Keywords : individual characteristics, job characteristics, organizational characteristics, job motivation, job satisfaction.